A new tyrannosauroid from the Upper Cretaceous of Shanxi, China. (April 2020) - Wu, Xiao-Chun; Shi, Jian-Ru; Dong, Li-Yang; Carr, Thomas D.; Yi, Jian; Xu, Shi-Chao
Abstract: Since 1983, only herbivorous dinosaurs and some isolated teeth of theropods have been described from the Upper Cretaceous of Shanxi Province, China. Here we report a new tyrannosauroid from the Upper Cretaceous of the province mainly based on a pair of maxillae and an associated dentary. This new dinosaur, named Jinbeisaurus wangi gen. et sp. nov., in addition to representing the first theropod dinosaur so far found in Shanxi Province it also adds to the known diversity of tyrannosauroids in Asia. J . wangi can be identified mainly by a broad interfenestral strut, a deep fossa on the broad base of the septum between the promaxillary recess and maxillary antrum, a low position of the dorsal row of dentary foramina, a similar number of denticles per unit length on both the mesial and distal carinae of the upper and lower teeth, and an acute angle of about 70° between the posterior process of the foot and the shaft of the pubis. J . wangi is a small to medium-sized theropod and phylogenetically more derived than Suskityrannus of North America within Tyrannosauroidea, probably even more derived than Xiongguanlong baimoensis from Gansu Province, China.